A bodipy based dual functional probe for the detection of hydrogen sulfide and H2S induced apoptosis in cellular systems1. Issue 54 (11th July 2015) - Gupta, Neha; Reja, Shahi Imam; Bhalla, Vandana; Gupta, Muskan; Kaur, Gurcharan; Kumar, Manoj
<x xml:space="preserve">Abstract</x> A bodipy based dual functional probe 1 has been designed and synthesized, which selectively detects H2S as well as monitors H2S induced apoptosis in cells.